The THE INFLUENCE OF CERTIFICATION, HALAL AWARENESS OF PRODUCTS AND BRAND IMAGE ON INTEREST IN REPURCHASING LIQUID PRODUCTS IN PT. NIPPON SHOKUBAI INDONESIA: CERTIFICATION, HALAL AWARENESS OF PRODUCTS AND BRAND IMAGE ON INTEREST IN REPURCHASING LIQUID PRODUCTS IN - Yoebrilianti, Anggit; Safitri, Ririn Safitri; Nurhayani, Nurhayani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to determine the effect of halal certification, halal product awareness and brand image on interest in repurchasing liquid products at PT. Nippon Shokubai Indonesia. This research was conducted using quantitative, descriptive and associative types. The population of this research is domestic consumers registered at the Distribution Department of PT. Nippon Shokubai Indonesia as many as 40 people using purposive sampling techniques. The research was conducted at PT. Nippon Shokubai Indonesia Ciwandan, Cilegon, Banten. Based on the research results, it can be concluded that the three independent variables, namely, halal certification, halal product awareness and brand image, ihave a positive and significant effect on interest in repurchasing liquid products at PT. Nippon Shokubai Indonesia. This means that the halal certification, halal product awareness and PT brand image are getting better. Nippon Shokubai Indonesia has resulted in higher consumer repurchase interest.